1975
DOI: 10.1080/03015521.1975.10425811
|View full text |Cite
|
Sign up to set email alerts
|

V. Gisborne Plains

Abstract: Pasture growth rates are presented for a site at Manutuke on the Gisborne Plains. Growth '"Cces were obtained over 27 years from a grazing trial cut by a standard method using a movable cage technique. The mean yield and standard error of individual samples over all years of measurement are given for standard dates at 14-day intervals. The seasonal pattern of growth had a spring peak, fluctuated over summer and autumn, and declined ever the winter. On average 17% of the annual growth was produced in winter (Ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1976
1976
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 5 publications
(2 reference statements)
1
4
0
Order By: Relevance
“…The Ruanui and Nui plots confirm work of Harris et al (1973) and Radcliffe (1974) which has shown that the percentage legume in Southland pastures in low compared with other regions in New Zealand (Brougham, 1960;Radcliffe, 1975a, b;Radcliffe and Sinclair, 1975;Baars et al, 1975). This low legume content and poor pasture growth in the late summer-autumn period causes problems on many Southland farms, in getting lambs to killing weight before there is competition for feed for flushing ewes prior to tupping.…”
Section: Discussionsupporting
confidence: 82%
“…The Ruanui and Nui plots confirm work of Harris et al (1973) and Radcliffe (1974) which has shown that the percentage legume in Southland pastures in low compared with other regions in New Zealand (Brougham, 1960;Radcliffe, 1975a, b;Radcliffe and Sinclair, 1975;Baars et al, 1975). This low legume content and poor pasture growth in the late summer-autumn period causes problems on many Southland farms, in getting lambs to killing weight before there is competition for feed for flushing ewes prior to tupping.…”
Section: Discussionsupporting
confidence: 82%
“…1. The average period of soil moisture deficit, normally during January-March, is 47 days (Radcliffe & Sinclair 1975).…”
Section: Methodsmentioning
confidence: 99%
“…1. The average period of soil moisture deficit, normally during January-March, is 47 days (Radcliffe & Sinclair 1975). The six steps contributing to development of the value proposition in this study are outlined below, with a more detailed description of methods following:…”
Section: Modelling Of Seasonal Pasture Supplymentioning
confidence: 99%
See 1 more Smart Citation
“…The ideal combination of ryegrass and white clover defies definition and is likely to vary from situation to situation. However, the importance of perennial ryegrass in New Zealand pastures can be seen in Table 1, which shows the percentage contribution of the ryegrass to the annual pdsture dry matter (DM) yields reco'rded in rate-of-growth mowing studies (Radcliffe, 1974a(Radcliffe, , 1974b(Radcliffe, , 1975(Radcliffe, , 1976Radcliffe and Sinclair, 1975;Baars et al, 1975;Baars, 1976;Round-Turner et al, 1976). These represent long-term-studies which have been conducted throughout New Zealand on improved pastures.…”
Section: Introductionmentioning
confidence: 99%